KEPASTIAN HUKUM DI INDONESIA TERKAIT PERLINDUNGAN DAN PEMBATASAN KEBEBASAN BERPENDAPAT PADA DUNIA MAYA (CYBERSPACE) - Richard Jatimulya Alam Wibowo; Rasji Rasji (Fakultas Hukum Universitas Tarumanagara, 2022)
The development of information and communication technology has brought cyberspace to bemore relevant in the media for delivering opinions. In this case, the constitution mandates thegovernment to play a role in protecting, upholding, and guaranteeing human rights, one of whichis freedom of opinion. The research was conducted using a normative juridical method with astatutory approach, tracing primary and secondary legal sources in the form of legislation, journalarticles, and jurisprudence. Legislation not only guarantees freedom of expression as a humanright, but also provides limitations so that freedom of expression is not used to violate the rights ofothers. Article 28E paragraph (3), 28F, and 28I paragraph (1) of the 1945 Constitution of theRepublic of Indonesia provide guarantees, while Article 28J paragraph (1) also provideslimitations. Furthermore, this limitation is given in the law which regulates the expression ofopinion in public, human rights, the press, as well as information and electronic transactions. Thattechnological developments not only bring convenience in expressing opinions, but also causeproblems due to the emergence of new actions and forms of expression that have never existedbefore. Therefore, this study aims to find gaps, shortcomings, and the need for regulationsregarding guarantees and restrictions on freedom of expression in cyberspace in the corridor ofhuman rights.